2013
DOI: 10.2147/cia.s47121
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker implantation complication rates in elderly and young patients

Abstract: AimsTo evaluate the complication rate differences between elderly and younger patients who receive a permanent pacemaker implantation.MethodsWe reviewed all cases admitted to our institution between January 2008 and June 2009 with symptomatic bradyarrhythmia for whom a permanent pacemaker was implanted. Beginning in June 2009, we prospectively collected data from all patients with the same diagnosis and procedure. The frequency of complications due to the pacemaker implantation procedure was evaluated and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Similarly, very elderly patients did not seem to have more complications than younger patients in other studies . On the contrary, Ozcan et al demonstrated that the complication rate for elderly patients who had a permanent PM implantation was statistically lower than in patients who were <70 years . However, in the largest epidemiologic study published so far about PM implantations, in the nonagenarians subgroup, including more than 12 000 patients from the Healthcare Cost and Utilization Project Nationwide Inpatient Sample administrative database, Mandawat et al demonstrated 1.87% and 6.31% mortality and complication rates, respectively, modestly but significantly more than in septuagenarians and octogenarians.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, very elderly patients did not seem to have more complications than younger patients in other studies . On the contrary, Ozcan et al demonstrated that the complication rate for elderly patients who had a permanent PM implantation was statistically lower than in patients who were <70 years . However, in the largest epidemiologic study published so far about PM implantations, in the nonagenarians subgroup, including more than 12 000 patients from the Healthcare Cost and Utilization Project Nationwide Inpatient Sample administrative database, Mandawat et al demonstrated 1.87% and 6.31% mortality and complication rates, respectively, modestly but significantly more than in septuagenarians and octogenarians.…”
Section: Discussionmentioning
confidence: 89%
“…Implantation of permanent pacemaker in the elderly has been reported to have higher complications rates than in younger patients; however, other researchers found that the rate of implant complications is comparable to and even less than that of younger patients.…”
Section: Discussionmentioning
confidence: 95%
“…Pacemaker implantation is performed for bradyarrhythmia patients of all ages, especially in the elderly population. [ 6 ] Approximately 70% to 80% of all pacemaker implantations are done for patients older than 65 years of age. [ 6 ] Fifteen percent of pacemakers in use are replacements, of which one fifth have been replaced more than twice.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Approximately 70% to 80% of all pacemaker implantations are done for patients older than 65 years of age. [ 6 ] Fifteen percent of pacemakers in use are replacements, of which one fifth have been replaced more than twice. [ 7 ] Although this procedure is safe, elderly subjects may have more postprocedural complications than younger subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation